2021
DOI: 10.1038/s41467-021-24171-z
|View full text |Cite
|
Sign up to set email alerts
|

Nucleation of protein mesocrystals via oriented attachment

Abstract: Self-assembly of proteins holds great promise for the bottom-up design and production of synthetic biomaterials. In conventional approaches, designer proteins are pre-programmed with specific recognition sites that drive the association process towards a desired organized state. Although proven effective, this approach poses restrictions on the complexity and material properties of the end-state. An alternative, hierarchical approach that has found wide adoption for inorganic systems, relies on the production … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 46 publications
2
23
0
Order By: Relevance
“…The crystal lamellae are in perfect structural registry, and the guanine composite thus resembles a mesocrystal. [ 30,47 ] We do not know if the same formation mechanism is employed in other guanine systems. However, it was recently observed that forming guanine crystals in hatchling lizards comprise ≈12 nm crystal plates, [ 21 ] which eventually merge into single crystals.…”
Section: Discussionmentioning
confidence: 99%
“…The crystal lamellae are in perfect structural registry, and the guanine composite thus resembles a mesocrystal. [ 30,47 ] We do not know if the same formation mechanism is employed in other guanine systems. However, it was recently observed that forming guanine crystals in hatchling lizards comprise ≈12 nm crystal plates, [ 21 ] which eventually merge into single crystals.…”
Section: Discussionmentioning
confidence: 99%
“…However, the nucleation of proteins does not have to be a two-step process. Van Driesch et al observed the direct self-assembly of glucose isomerase protein molecules into polyhedral nanocrystals with surprising smooth surfaces and sharp vertices, indicating a one-step nucleation mechanism [80]. The more detailed theoretical developments of the two-step nucleation mechanism can be found here [81,82].…”
Section: Two-step Nucleation Mechanismmentioning
confidence: 89%
“…Recent studies show citrate altering the nucleation pathway of calcium oxalate hydrates by interacting with pre-nucleation aggregates and amorphous intermediates mainly through water incorporation and local structure ordering [158]. More recently, multiple nucleation pathways are also seen in protein systems [31,80]. Multiple nucleation pathways were previously suggested by De Yoreo [64] in explaining the nucleation behavior of an inorganic system.…”
Section: Aggregation-based Multiple Nucleation Pathwaysmentioning
confidence: 94%
See 1 more Smart Citation
“…However, the classical nucleation theory (CNT) fails to explain the crystallization mechanism of many organic molecules. , The crystallization of organic molecules is more complicated than that of inorganic materials because the conformational degrees of freedom in molecular systems introduce dynamical factors that render them distinct from inorganic systems . Nonclassical crystallization, also known as crystallization by particle attachment, , is now recognized as a predominant crystallization pathway for many organic compounds ranging from small molecules to proteins. Amorphous precursor phases are formed as metastable intermediates via two-step nucleation before substantial crystallization. Apart from the conventional monomer-by-monomer crystal growth mechanism, small nanocrystals can grow via a so-called “oriented attachment” pathway, which refers to the spontaneous self-organization and fusion of adjacent nanocrystals by sharing a common crystallographic orientation . Oriented attachment reduces the surface energy and thus thermodynamically lowers the enthalpy of the system .…”
mentioning
confidence: 99%